Evaluation of Verticutting and Herbicides for Tropical Signalgrass (Urochloa subquadripara) Control in Turf. (2nd May 2018) - Pearsaul, David G.; Leon, Ramon G.; Sellers, Brent A.; Silveira, Maria L.; Odero, D. Calvin
Abstract: Tropical signalgrass (TSG) is one of the most problematic weeds found on golf courses, sports fields, and sod farms in south Florida. The recent ban of monosodium methane-arsonate (MSMA), an organic arsenical herbicide, from urban areas in Florida has left turfgrass managers searching for effective management options. In an effort to avoid relying solely on POST chemical control, this research examined the effect of combining a cultural practice, verticutting, along with PRE and POST herbicides as an integrated weed management approach to controlling TSG in hybrid bermudagrass. Field experiments were conducted at multiple locations over 2 yr in south Florida to: (1) determine whether verticutting before herbicide applications increases TSG control and (2) identify herbicide programs that effectively control TSG. No interactions between verticutting and herbicide programs were detected, but verticutting consistently provided a slight reduction (8% averaged across herbicide treatments) in TSG cover. Treatments containing a PRE herbicide resulted in a significant reduction (20% to 50%) in TSG cover at 52 wk after initial treatment (WAIT), while some POST herbicide treatments reduced TSG cover to <20% at 52 WAIT. A study was conducted to determine which POST herbicide combinations were most efficacious in controlling TSG. Amicarbazone alone provided ≤35% TSG control at 8 and 12 WAIT, but synergistic responses were observed between amicarbazone and mesotrione, trifloxysulfuron, and thiencarbazone+foramsulfuron+halosulfuron. Two- and three-way combinations of amicarbazone with these POST herbicides resulted in >80% TSG control at 4, 8, and 12 WAIT, with some reaching 100% TSG control at 4 WAIT. Based on these data, verticutting may provide limited complementary control, but certain combinations of POST herbicides exhibited excellent (>95%) TSG control.